Measuring the fate of different diluted bitumen products in coastal surface waters. (April 2020) - Ortmann, Alice C.; Cobanli, Susan E.; Wohlgeschaffen, Gary; MacDonald, Jessica; Gladwell, Alison; Davis, Andrew; Robinson, Brian; Mason, Jennifer; King, Thomas L.
Abstract: Diluted bitumens are produced by adding lower viscosity diluent to highly viscous bitumen to enable it to flow through pipelines and thus may behave differently than conventional oils when spilled into coastal seawater. Simulated surface spills using three different diluted bitumen products were carried out in May, July and November and water column hydrocarbons were monitored over a 14 day period. Volatile and total petroleum hydrocarbons varied in the water column depending on season and type of diluent. In summer, products diluted with synthetic crude or a mixture of condensate and crude released droplets into the water column. Diluted bitumen did not sink to the bottom of the enclosures with surface slicks showing a range of weathering after 14 d. With most of the diluted bitumen product remaining on the surface for 14 d, a rapid conventional clean up response may be effective in low energy, coastal waters. Graphical abstract: Unlabelled Image Highlights: Season and diluent affect hydrocarbon concentrations in the water below a spill Droplets were released into the water column in summer with some diluents Sinking of weathered diluted bitumen did not occur under experimental conditions Concentrations of PAHs were 10 fold lower than those that cause toxicity